Non-O157:H7 Shiga toxin-producing Escherichia coli in bovine rectums and surface water streams on a beef cattle farm in Argentina - Tanaro, J D (2012)
Fil: Tanaro, J D. Universidad Nacional de Entre Ríos. Facultad De Bromatología,, Gualeguaychú. Cátedra de Microbiología; Argentina.